ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PENGETAHUAN KELUARGA TENTANG COVID-19 DI PROVINSI BANTEN TAHUN 2020 - Ahmad Ahmad; Suhartini Suhartini (Jurnal Medikes (Media Informasi Kesehatan), 2021)
Coronavirus Disease 2019 (COVID-19) is a contagious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This is a new type of coronavirus that has never been previously identified in humans. The COVID-19 cases in various province in Indonesia has increased significantly. Based on the data from Banten Provincial Public Health Office, as of July 25, 2020, there were 10.456 cases of ODP (people under monitoring), 3.364 cases of PDP (patient under surveillance), 1.244 positive cases, and 98 deaths. This study aims to determine the factors that influence family knowledge about COVID-19 in Banten Province, 2020. The research design is cross-sectional with a population of people who are respondents in integrated PKL (field work training) activities. The data used is secondary data from the result of integrated PKL students on 302 respondents. The research sample is 178 with criteria; the respondents live in Banten Province, the data analysis was carried out using univariate and bivariate. The results showed that the proportion of respondents who had a good level of knowledge about COVID-19 was slightly higher (59,6%) compared to respondents who had less knowledge of COVID-19 (40,4%). Most of the respondents are >30 years old (83,3%), have low education (68%), female (83,3%), and live in the district (82%). The knowledge about COVID-19 was highly obtained from non-health workers (64%), more than half of the respondents lived in the green zone (61,2%), while a small proportion of the respondents lived in the red zone (27%). The results also show that there is a significant relation between education and family knowledge about COVID-19 with OR value 10,2. There is also relation between sources of information and family knowledge about COVID-19 with OR value 34,2. However, there is no relation between ages, gender, and places where they lived, with family knowledge about COVID-19. Sosialization and education on preventing COVID-19 with 3 messages (wearing mask, washing hands with soap, and keeping the distance) need to be carried out through various media such as brochures, leaflets, posters, banners, and any other media.